Bendungan Bili-Bili 1992-2016 - Jamaluddin, Jamaluddin (Universitas Negeri Makassar, 2018)
The study aims at discovering (i) the background of Bili-Bili dam construction, (ii) The development of Bili-Bili dam annually and (iii) the impact of Bili-Bili dam construction for the local people. The results of the study reveal the (i) Beckround of the construction Bili-Bili dam, because the city ofÂ Ujung Pandang and Sungguminasa almost every year hit bay floods, so the goverment conducted a technical review to evercome the problem. From the results the study was initiated the need to build dam to cope with flooding, fulfill the need of clean water for urban society, the needs of industrial water, the need of farming, and the needs of electrical energy, (ii) The development of the Bili-Bili dam takes place in three stages: first phase of technical studies in 1986-1988. The second phase of phisical construction of the dam in 1992-1999. Third stage of management and maintenance in 2000 until now. (iii) The Bili-Bili dam construction gave positif benefits for Makassar people, Sungguminasa people, and some of the people who live around the dam, but not for the people who good infect with the Bili-Bili dam project such as unclear land compensation and loss of farming culture its tradition